Effect of Early and Late Interventions with Dietary Oils on Vascular and Neural Complications in a Type 2 Diabetic Rat Model. (7th August 2019) - Coppey, Lawrence; Davidson, Eric; Shevalye, Hanna; Obrosov, Alexander; Yorek, Mark
Abstract : Aims . Determine the effect of dietary oils enriched in different mono- or polyunsaturated fatty acids, i.e., olive oil (18 : 1, oleic acid), safflower oil (18 : 2 n-6, linoleic acid), flaxseed oil (18 : 3 n-3, alpha linolenic acid), evening primrose oil (18 : 3 n-6, gamma linolenic acid), or menhaden oil (20:5/22 : 6 n-3 eicosapentaenoic/docosahexaenoic acids), on vascular and neural complications in high-fat-fed low-dose streptozotocin-treated Sprague-Dawley rats, an animal model for late-stage type 2 diabetes. Materials and Methods . Rats were fed a high-fat diet (45% kcal as fat primarily derived from lard) for 8 weeks and then treated with a low dose of streptozotocin (30 mg/kg) in order to induce hyperglycemia. After an additional 8 (early intervention) or 20 (late intervention) weeks, the different groups of rats were fed diets with 1/2 of the kcal of fat derived from lard replaced by the different dietary oils. In addition, a control group fed a standard diet (4.25% kcal as fat) and a diabetic group maintained on the high-fat diet were maintained. The treatment period was approximately 16 weeks. The endpoints evaluated included vascular reactivity of epineurial arterioles, motor and sensory nerve conduction velocity, thermal and corneal sensitivity, and innervation of sensory nerves in the cornea and skin. Results . Our findings show that menhaden and flaxseed oil provided the greatest benefit for correcting peripheral nerve damage caused by diabetes, whereas enriching the high-fat diet with menhaden oil provided the most benefit to acetylcholine-mediated vascular relaxation of epineurial arterioles of the sciatic nerve. Enriching the diets with fatty acids derived from the other oils provided none to partial improvements. Conclusions . These studies imply that long-chain n-6 and n-3 polyunsaturated fatty acids could be an effective treatment for diabetic peripheral neuropathy with n-3 polyunsaturated fatty acids derived from fish oil being the most effective.